Exploring stories of learning and professional development: interactions between GP personal tutors and medical students. Issue 5 (2nd September 2020) - Abrams, R; Sriranjan, A; Park, S; Coppola, W; Ferris, M.
ABSTRACT: Background: The demanding environment at medical school results in some students being prone to a high risk of mental health issues. GMC recommendations include positioning personal tutors for pastoral support and to act as academic role models. Tutors who are clinicians, such as GPs, could help students develop their academic and professional narratives. Our study explores interactions between GP tutors and students and evaluates how personal tutoring can support the ways in which students respond to the medical school culture and its demands. Method: Six pairs of GP tutors and medical students had three personal tutor meetings over 9 months. Twelve meetings were recorded. A dialogical narrative analytical approach was used to assess how students' problems and reflective processes were negotiated with tutors. Three themes were formed to consolidate findings. Results: Tutors' affirmations helped students develop an alternative narrative to perfectionism focusing on 'doing well' and self-care. Reflection on students' perceptions of a medical career were prompted by tutors who encouraged students to keep an open-minded and enthusiastic outlook. Active participation from students sometimes required tutors to relinquish hierarchical power and share personal experiences. Conclusion: GP tutors can help reframe student narratives of perfectionism and professionalism by expressing their vulnerabilities and working collaboratively. With clear guidance, there is potential for personal tutors working as GPs, to benefit students in the long run both academically and professionally. However, this should go hand in hand with a transformation of medical school culture to prevent sole focus on building student resilience.